(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
SOMMARIO: 1. Premessa: la laicità giuridica - 2. L’enunciazione - 3. La definizione - 4. La riscrittura. Abstract: In his brilliant work on «La laicità penale alla sfida del "secolo delle paure"» Carlo Enrico Paliero highlighted the distance between positive legal systems and a supposed (ideal-typical) archetype of ’laicità’, of which the single legal system represents a "mestizo" model. The iconic image restores the complexity of any definitional challenge on ’laicità’. Law, unfolding as a practical science, has gradually managed to circumvent the obstacle through a process of empirical signification, derived, at times, from concrete needs. Therefore, it would be improper, if not arbitrary, to attempt to offer a contribution on legal ’laicità’ in disregard of the events that have characterized its absence from the text of the Charter and the demands of ordinal self-protection that have determined, instead, the subsequent ’unveiling’ or ’creation’ of the unexpressed principle.